Investigating the role of age and maturation on the association between tennis experience and cognitive function in junior beginner to intermediate-level tennis players. Issue 5 (October 2022) - Turner, Mitchell; Ishihara, Toru; Beranek, Philipp; Turner, Kate; Fransen, Job; Born, Philipp; Cruickshank, Travis
Sport engagement, including tennis, and physical activity have been shown to have a positive influence on cognition in children. However, age has also been found to have a strong association with cognition in youth athletes. This study examines the threshold hypothesis by investigating the moderating role of age and maturation on the association between tennis experience and cognitive measures in Australian and German junior beginner to intermediate-level tennis players. The demographic information, which includes years of tennis experience, and anthropometrics (e.g. height and weight) was collected for 48 junior tennis players. A comprehensive cognitive testing battery was then completed to assess cognitive performance, with a principle component analysis used to determine an overall cognitive performance score. Multiple regression analyses were then performed to test the relationship between tennis experience and cognitive performance as well as the moderating effects of age and maturation. The results of this study indicate that the age and maturation rather than the exposure to tennis training are related to cognitive performance. Additionally, the positive relations of tennis experience to cognitive performance were stronger in younger participants, specifically those younger than 12 years old. Therefore, tennis may not provide a stimulus large enough for further cognitive improvement once players have developed a high level of cognitive performance. While age and biological maturity will largely dictate cognitive performance in adolescents, tennis experience may play some role in the cognitive performance of children (specifically <12 years of age).